SIRT3 blocks myofibroblast differentiation and pulmonary fibrosis by preventing mitochondrial DNA damage - Bindu, Samik (Am J Physiol Lung Cell Mol Physiol, 2017)
Myofibroblast differentiation is a key process in the pathogenesis of fibrotic diseases. Transforming growth factor-β(1) (TGF-β(1)) is a powerful inducer of myofibroblast differentiation and is implicated in pathogenesis of tissue fibrosis. This study was undertaken to determine the role of mitochondrial deacetylase SIRT3 in TGF-β(1)-induced myofibroblast differentiation in vitro and lung fibrosis in vivo. Treatment of human lung fibroblasts with TGF-β(1) resulted in increased expression of fibrosis markers, smooth muscle α-actin (α-SMA), collagen-1, and fibronectin. TGF-β(1) treatment also caused depletion of endogenous SIRT3, which paralleled with increased production of reactive oxygen species (ROS), DNA damage, and subsequent reduction in levels of 8-oxoguanine DNA glycosylase (OGG1), an enzyme that hydrolyzes oxidized guanine (8-oxo-dG) and thus protects DNA from oxidative damage. Overexpression of SIRT3 by adenovirus-mediated transduction reversed the effects of TGF-β(1) on ROS production and mitochondrial DNA damage and inhibited TGF-β(1)-induced myofibroblast differentiation. To determine the antifibrotic role of SIRT3 in vivo, we used the bleomycin-induced mouse model of pulmonary fibrosis. Compared with wild-type controls, Sirt3-knockout mice showed exacerbated fibrosis after intratracheal instillation of bleomycin. Increased lung fibrosis was associated with decreased levels of OGG1 and concomitant accumulation of 8-oxo-dG and increased mitochondrial DNA damage. In contrast, the transgenic mice with whole body Sirt3 overexpression were protected from bleomycin-induced mtDNA damage and development of lung fibrosis. These data demonstrate a critical role of SIRT3 in the control of myofibroblast differentiation and lung fibrosis.